Keanekaragaman Famili Poaceae Di Wilayah Kampus I UIN Sunan Gunung Djati Bandung - Anggi Agustin; Anita Fitriyani; Lindiyani Lindiyani; Ateng Supriatna (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
This research aims to identify and document the diversity of Poaceae species on Campus I UIN Sunan Gunung Djati Bandung. The Poaceae family, or grasses, have an important role in ecosystems, agriculture and the economy. This study uses direct exploration methods to observe and collect data about Poaceae species in the campus area. A total of 13 types of plants from the Poaceae family were identified, with most of them being herbaceous and one species being a tree, namely Bambusa multiplex. The Poaceae species diversity index in this area was calculated using the Shannon-Wiener formula, which shows an H' value of 2.51, indicating moderate species diversity. The results of this research provide in-depth insight into ecosystem dynamics in the campus area and support efforts to conserve biodiversity through better management strategies.